The Impact of Quantum Computing on Cryptographic Protocols - Adamson, Millie (My University, 2025)
This thesis explores the impact of quantum computing on the security of e-voting, using Estonia’s e-voting system as a case study. Chapters 1 and 2 provide insight into the development of quantum computing and why this threatens contemporary cryptography. Chapter 3 reviews the current e-voting protocol used in Estonia. Chapter 4 considers the challenges and urgency of migrating to post quantum e-voting. Then, chapters 5 and 6 explore potential quantum safe alternatives to contemporary cryptography, in particular exploring the use of lattice based hard problems. Chapters 7 and 8 provide insight into proposed post quantum solutions specific to e-voting and the current challenges faced with their implementations.
Keywords: cryptography, post-quantum cryptography, Shor’s Algorithm, e-voting, ML-KEM